Game-theoretical, Strategic forward Contracting in the Electricity Market - Pär Holmberg (Research Institute of Industrial Economics (IFN), 2008)
Forward sales is a credible commitment to aggressive spot market bidding, and it mitigates producers market power in electricity markets. Still it can be profitable for a producer to make such a commitment if it results in a soft response from competitors in the spot market (strategies are substitutes). The optimal contracting level of a risk-neutral producer is determined by the extent to which strategies are substitutes and the slope of the residual demand in the forward market. Conditions under which strategies are substitutes are identified for a two-stage game with supply function competition and capacity constrained producers.
Keywords: C72; D43; D44; G13; L13; L94; 330; Supply Function Equilibrium; Forward Market; Strategic Contracting; Arbitrage; Strategic Substitutes; Oligopoly; Electricity Market; Energiehandel; Oligopol; Derivat; Angebot; Spieltheorie; Theorie